Can there be an Asian model of public administration - Cheung, Anthony B.L. (2013)
This article examines the conceptual possibilities of an Asian model of public administration, challenging some pre-established paradigms along the way. There are two basic contentions. First, there is no such thing as one universal model of public administration that satis?es all national political and cultural situations so that each public administration system is also shaped by its own national tradition and historical evolution. The historical process is as important as the horizontal process of policy learning and transfer from others in the world. Second, Asia has its unique administrative civilization that has been under-studied in the larger context of contemporary public administration theories and practices. The article does not argue for an Asian-dominated governance model per se. Rather, the point is that the rapid social and economic growth of some emerging Asian nations has cast further doubt on any deterministic 'good governance' model driven predominantly by the Western growth experience. No de?nite thesis is concluded, and this must involve a process of drawing wisdoms from more Asian 'national' and local narratives of administrative histories and practices. - Reproduced.
Keywords: Public administration